Balancing Linguistic Goals and Community Relevance: Lessons from Documenting the Baduy dalam Sundanese Language - Hernawan; Eri Kurniawan; Retty Isnendes; Rd. Dian Dia-an Muniroh; Haris Santosa Nugraha; Bradley McDonnel; Michael Ewing (Linguistik Indonesia, 2025)
Language documentation plays a critical role in preserving linguistic diversity and cultural heritage. However, balancing the academic goals of linguists with the practical needs and interests of indigenous communities remains a challenge. This study reports on the first phase of documenting the relatively isolated indigenous language of Baduy Dalam in Banten, Indonesia. Using a linguist-centered approach, the fieldwork involved eliciting language data and recording daily narratives, culminating in the creation of a small Baduy dictionary. While the project succeeded in capturing targeted word forms and sentence structures, local informants expressed concerns about its relevance to their community. These findings highlight the limitations of linguist-driven documentation efforts, suggesting the need for approaches that prioritize community engagement and shared ownership of language preservation initiatives. A shift towards community-based and multidisciplinary methodologies may foster greater participation, ensuring that language documentation aligns with both academic and local community objectives.